Kajian Peraturan Protokol Kesehatan Bagi Perorangan Serta Penegakannya - Krisantiwi Meira Anggarini (Masyarakat Hukum Kesehatan Indonesia, 2022)
Presidential Instruction of the Republic of Indonesia Number 6 of 2020 on Enhancing Self-Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Corona Virus Disease 2019 mandates Governors, Regents and Mayors to formulate and stipulate regulations containing provisions on health protocols for individuals, business actors, administrator, organizer or person in charge of public places and facilities. From the Presidential Instruction, various regulations were born in each region to be implemented in their respective regions, one of which is the Semarang Mayor Regulation Number 49 of 2021 on the Implementation of Public Activity Restrictions in the Prevention and Control of Corona Virus Disease 2019 in Semarang City. However, the regulation has several loopholes which if not analyzed further and revised, can make it difficult to enforce them, thus health protocols become slack and potentially lead to a fatal condition where cases number increased again as is currently happened in several countries, including the European Union.